Festival Women Ngalam Bergerak sebagai Wadah Penggerak Aktivisme Feminis di Malang Raya - Lasari, Yuni; Dewi, Sulih Indra (Unitri Press, 2025)
This study aims to analyze how the Women Ngalam Bergerak Festival serves as a driving force for feminist activism in Malang Raya. Initiated by Paguyuban Literasi Malang to commemorate International Women’s Day 2024, the festival responds to the lack of safe spaces and limited participation of women in local public discourse. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that the festival is not merely a symbolic celebration, but a collaborative space that facilitates the exchange of feminist discourses across various backgrounds, including activists, academics, artists, and marginalized communities. The festival featured activities such as safe space forums, open-mic sessions, art exhibitions, feminist book discussions, and cloth pad workshops—each serving as platforms for healing, advocacy, and education. It also catalyzed the formation of a new community, “Women Ngalam Bergerak,” which continues to hold monthly discussions, internal classes, and community-based advocacy. The study highlights the characteristics of a new social movement present in the form of horizontal relations, cross-gender participation, and collective awareness of the importance of safe spaces and transformative justice. This festival demonstrates that safe spaces and feminist discourse can be built from the ground up through organized, conscious, and collaborative community work. Abstrak Penelitian ini bertujuan menganalisis bagaimana Festival Women Ngalam Bergerak menjadi wadah penggerak aktivisme feminis di Malang Raya. Festival ini digagas oleh Paguyuban Literasi Malang dalam rangka memperingati Hari Perempuan Internasional 2024, dan dilatarbelakangi oleh minimnya ruang aman serta terbatasnya partisipasi perempuan dalam diskursus publik lokal. Menggunakan pendekatan studi kasus kualitatif, data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi. Hasil penelitian menunjukkan bahwa festival ini tidak hanya menjadi perayaan simbolik, melainkan ruang kolaboratif yang memfasilitasi pertukaran wacana feminisme lintas latar belakang: aktivis, akademisi, seniman, serta komunitas marjinal. Festival menghadirkan forum diskusi bertema ruang aman, mimbar bebas, pameran karya, review buku feminis, hingga workshop pembalut kain, yang semuanya menjadi media pemulihan, advokasi, dan edukasi. Festival ini juga memicu lahirnya komunitas baru “Women Ngalam Bergerak” yang secara berkelanjutan mengadakan diskusi bulanan, kelas internal, dan advokasi berbasis komunitas. Temuan mengindikasikan bahwa karakteristik new social movement hadir dalam bentuk relasi horizontal, partisipasi lintas gender, serta kesadaran kolektif terhadap pentingnya ruang aman dan keadilan transformatif. Festival ini membuktikan bahwa ruang aman dan wacana feminisme dapat dibangun dari bawah melalui kerja kolaboratif komunitas yang sadar dan terorganisir.